(untitled) (Journal of responsible AI & ethics, 2026)
The use of Artificial Intelligence (AI) has revolutionized various industries, but its potential to address environmental sustainability challenges remains under-explored. This paper delves into the ethical implications of using AI in environmental contexts and examines how technology can contribute to achieving sustainability goals. The study investigates how AI applications, such as machine learning, data analytics, and predictive modeling, can enhance resource management, pollution reduction, and climate change mitigation efforts. The paper emphasizes the importance of ensuring responsible AI practices by discussing the role of transparency, accountability, and equity in deploying AI solutions in environmental sectors. Additionally, it explores the need for a robust ethical framework that aligns AI development with the principles of sustainability. Through case studies, empirical data, and theoretical analysis, the paper outlines the intersection of AI technology and environmental ethics, highlighting both opportunities and challenges. The study concludes by providing recommendations for promoting sustainable AI and enhancing the role of AI in building a sustainable future while adhering to ethical standards.